2021
DOI: 10.1016/j.jneumeth.2020.108951
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of diffusion MRI to microstructural properties and experimental factors

Abstract: Highlights This work reviews different methods for studying brain microstructure using dMRI. Sensitivity to microstructural differences and experimental factors is investigated. Signal representation-based methods and multi-compartment models are explained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 377 publications
(334 reference statements)
0
56
0
Order By: Relevance
“…Various diffusion indices are used across the literature, including fractional anisotropy (FA), mean diffusivity (MD), number of streamlines, and voxels intersected by streamlines as a proxy of volume. These indices have been associated with microstructural properties and have been used to indicate axonal damage or degeneration (Beaulieu 2002;Ciccarelli et al, 2008;Afzali et al, 2021). Each index was extracted from the 326 studies and the results highlight that some measures are more commonly reported than others (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Various diffusion indices are used across the literature, including fractional anisotropy (FA), mean diffusivity (MD), number of streamlines, and voxels intersected by streamlines as a proxy of volume. These indices have been associated with microstructural properties and have been used to indicate axonal damage or degeneration (Beaulieu 2002;Ciccarelli et al, 2008;Afzali et al, 2021). Each index was extracted from the 326 studies and the results highlight that some measures are more commonly reported than others (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…A key application of QDI is in imaging of the human body where diffusion of free water at body temperature is D FW = 3 × 10 −3 mm 2 s −1 and 0.5 < α < 1 in typical healthy brain tissue [1]. Figure 1 illustrates the family of signal decay curves described by (10). Figure 1a shows the quasi-diffusion signal attenuation parameterised by b for an arbitrary diffusion coefficient, D 1,2 = 1.5 × 10 −3 mm 2 s −1 for 0.1 ≤ α ≤ 0.99 with Figure 1b showing the quasi-diffusion signal attenuation parameterised by q. with ≪ ∆.…”
Section: Quasi-diffusion Imagingmentioning
confidence: 99%
“…A key application of QDI is in imaging of the human body where diffusion of free water at body temperature is 3 10 mm 2 s −1 and 0.5 1 in typical healthy brain tissue [1]. Figure 1 illustrates the family of signal decay curves described by (10).…”
Section: Quasi-diffusion Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting models are called MC models and they require the acquisition of multi-shell dMRI data in order to accurately disentangle the contribution of each compartment (Scherrer and Warfield, 2010). Thorough reviews have been dedicated to the design and validation of such models (Jelescu and Budde, 2017), to the sensitivity of MC models to experimental factors and microstructural properties of the described tissues (Afzali et al, 2020), and to the abstraction of these models that allows to obtain a unified theory (Fick et al, 2019).…”
Section: Introductionmentioning
confidence: 99%